Effects of different stunning methods on the welfare and carcass quality of finisher pigs in South African pork abattoirs - Webb, E.C. (Edward Cottington) (University of Pretoria, 2024)
Dissertation (MSc Agric (Animal Science))--University of Pretoria, 2024.